Association between lipid lowering regimen intensity at discharge and long-term mortality in optimally-treated patients with acute myocardial infraction. The FAST-MI programme. (25th November 2020) - Danchin, N; Ferrieres, J; Puymirat, E; Cayla, G; Cottin, Y; Coste, P; Roubille, F; Furber, A; Albert, F; Schiele, F; Simon, T
Abstract: Background: Randomised trials evaluate the efficacy of individual medications, irrespective of overall patient management. We assessed the association between lipid-lowering therapy (LLT) intensity and long-term mortality in otherwise optimally-treated patients with acute myocardial infarction (AMI). Methods: FAST-MI consists in one-month nationwide French surveys of patients admitted for a recent AMI, repeated every 5 years. We used the 2010 and 2015 data with 3-year follow-up. Background optimal therapy was defined as use of PCI, together with ESC guideline-recommended treatment with beta-blockers, ACEi/ARB, when indicated, and optimal antithrombotic medications including type of P2Y12-i; of 9, 460 patients included, 4, 042 were optimally-treated, with 478 (12%), 1120 (28%), and 2, 444 (60%) respectively receiving conventional-dose statins (Gr 1), moderate-intensity statins (atorvastatin 40 mg or rosuvastatin 10 mg) (Gr2) or high-dose LLT (atorvastatin 80 mg, rosuvastatin ≥20 mg or statin-ezetimibe combination) (Gr3). Results: Baseline characteristics markedly differed in the 3 groups (Table 1). Three-year Kaplan-Meier survival was 88.5%, 93.5% and 96.3% respectively for gr 1, 2 and 3, with Cox-adjusted HR of 0.75 (0.51–1.10), P=0.137, and 0.59 (0.41–0.86), P=0.006 for gr 2 and 3 compared with Gr1 (Figure). Conclusion: In otherwise optimally-treated AMI patients, lipid-lowering regimen intensity at discharge was inversely associated with 3-year mortality. These results confirm that high-intensity lipid lowering therapy at discharge is likely beneficial even in patients receiving otherwise optimal therapy. Funding Acknowledgement: Type of funding source: Private grant(s) and/or Sponsorship. Main funding source(s): MSD, AstraZeneca